Personality disorder co-morbidity in primary care 'Improving Access to Psychological Therapy' (IAPT) services: a qualitative study exploring patient perspectives on treatment experience. Issue 2 (8th March 2021) - Lamph, Gary; Baker, John; Dickinson, Tommy; Lovell, Karina
Abstract: Background: High numbers of people present with common mental health disorders and co-morbid personality disorder traits in primary care 'Improving Access to Psychological Therapies' (IAPT) services in England and they receive sub-optimal treatments. No previous studies have explored the treatment experiences or needs of this patient population in England. Aims: This qualitative study explored the treatment experiences of patients ( n = 22) with common mental health difficulties and co-morbid personality disorder as indicated by a score of 3 or more on the 'Standardised Assessment of Personality – Abbreviated Scale' (SAPAS) in receipt of primary care-based IAPT treatment. Method: A qualitative health research approach was used. Qualitative individual face-to-face semi-structured interviews were conducted. All interviews were audio recorded, data were transcribed verbatim and analysed using a framework analysis approach. Results: Findings revealed a need to adapt away from prescriptive cognitive behavioural therapy (CBT) treatment models towards more flexible, personalised and individualised treatment with this patient group. Time to emotionally offload, build a therapeutic relationship and link past experiences to presenting problems were highlighted as important. Conclusions: For the first time, the needs and treatment experiences of this patient group have been explored. This paper provides a unique patient experience insight that should be considered when exploring new approaches to working with and developing effective interventions via a stepped care approach.